(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Size analysis of the Middle Miocene Lower Siwalik sediments comprising the Nahan Formation in the type area and adjoining regions reveals that the sediments are unimodal to polymodal in nature, dominantly fine grained and are moderately sorted. The log probability plot reveals that saltation mode is the dominant mode of transportation of detritus. The sediments are continental in character and derived from crystalline, metamorphic and sedimentary rocks of the Himalaya exposed to the North of the type area Nahan.